The short-term effects of non-surgical periodontal therapy on the circulating levels of interleukin-6 and C-reactive protein in patients with chronic periodontitis - Annie Kitty George; Prasanthila Janam (Wolters Kluwer Medknow Publications, 2013)
Background: Recent epidemiological studies have shown that periodontal infection is a risk factor for a number of systemic diseases and conditions. In addition to the conventional risk factors, chronic infection and the subsequent generation of a systemic inflammatory response may be associated with this increased risk. Aims: This study was conducted to determine whether the presence of chronic periodontitis and subsequent non-surgical periodontal therapy could influence the serum levels of interleukin-6 and C-reactive protein (CRP) in patients with severe chronic generalized periodontitis. Settings and Design: Participants were selected from subjects who attended the Department of Periodontics and Oral Implantololgy, Government Dental College, Thiruvananthapuram. Materials and Methods: Sera were obtained from 25 patients with periodontitis for baseline examination and reassessment after completion of treatment. As a control, sera were also obtained from 20 subjects without periodontitis. Interleukin-6 was determined by sensitive enzyme-linked immunosorbent assay, and high-sensitivity CRP (hsCRP) was measured using latex turbidometric immunoassay. Statistical Analysis: Data were analyzed using computer software, Statistical Package for Social Sciences (SPSS) version 10. Results: The level of interleukin-6 and hsCRP in the sera of periodontitis patients was seen to be higher than those of healthy controls. Interleukin-6 level tended to decrease with improvement of the periodontal condition following treatment and approached that of control subjects, and this decline was statistically significant. The hsCRP levels also showed a decreasing trend following periodontal treatment. Conclusions: In this study, we were able to show that periodontal disease significantly affects the serum levels of systemic inflammatory markers and that non-surgical periodontal therapy could bring about a decrease in the levels of these inflammatory markers.